2008
DOI: 10.1098/rspb.2007.1626
|View full text |Cite
|
Sign up to set email alerts
|

Males with high genetic similarity to females sire more offspring in sperm competition in Peron's tree frogLitoria peronii

Abstract: Recent work has confirmed that genetic compatibility among mates can be an important determinant of siring success in sperm competition experiments and in free-ranging populations. Most of this work points towards mate choice of less related mates. However, there may also be the potential for mate choice for intermediate or even genetically similar mates to prevent outbreeding depression or hybridization with closely related taxa. We studied relatedness effects on post-copulatory gametic choice and/or sperm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 50 publications
7
67
0
Order By: Relevance
“…Surprisingly, we also found no evidence that the proportion of viable sperm within a male's ejaculate affects siring success in sperm competition or in the single-species fertilizations (controls). This is consistent with our previous study on sperm competition in L. peronii (Sherman et al, 2008b), which showed that the only significant predictor of siring success in sperm competition trials is the corresponding success of males in control fertilizations. This suggests that some unmeasured intrinsic property of a male's sperm (or semen) is important in determining a male's siring success at fertilization.…”
Section: Trial Number Proportion Offspring Siredsupporting
confidence: 82%
See 3 more Smart Citations
“…Surprisingly, we also found no evidence that the proportion of viable sperm within a male's ejaculate affects siring success in sperm competition or in the single-species fertilizations (controls). This is consistent with our previous study on sperm competition in L. peronii (Sherman et al, 2008b), which showed that the only significant predictor of siring success in sperm competition trials is the corresponding success of males in control fertilizations. This suggests that some unmeasured intrinsic property of a male's sperm (or semen) is important in determining a male's siring success at fertilization.…”
Section: Trial Number Proportion Offspring Siredsupporting
confidence: 82%
“…Furthermore, the fact that L. peronii males more closely related with the female have a fertilization advantage also suggests that the risk of hybridization is real in the wild (Sherman et al, 2008b). We were, however, surprised at the complete hybrid compatibility at the gametic level-especially in a situation of sperm competition with another species.…”
Section: Trial Number Proportion Offspring Siredmentioning
confidence: 76%
See 2 more Smart Citations
“…In the guppy, sperm velocity in the ovarian fluid and fertilization success were higher for males unrelated to the female than for related (full-sib) males . Fertilization experiments in Arctic charr (Liljedal et al, 2008) revealed a higher fertilization success for males genetically less similar to the female, while in the Peron's tree frog (Sherman et al, 2008) fertilization success was biased towards males genetically more similar to the female. In contrast, in Lake Trout, sperm velocity was lower for males unrelated to the female than for related (full-sib) males (Butts et al, 2012).…”
Section: Introductionmentioning
confidence: 99%